Boosting effect of ortho-propenyl substituent on the antioxidant activity of natural phenols. (1st April 2016) - Marteau, Clémentine; Guitard, Romain; Penverne, Christophe; Favier, Dominique; Nardello-Rataj, Véronique; Aubry, Jean-Marie
Highlights: BDE calculations show that o -propenyl should increase phenol antioxidant activity. DPPH test highlights two opposite effects of o -propenyl substituent on phenols. o -Propenyl drastically increases the rate of hydrogen transfer from phenols. o -Propenyl decreases the number of DPPH radicals reduced per phenol molecule. Lower stoichiometry due to an unavailability of phenol at o - and p - positions. Abstract: Seven new antioxidants derived from natural or synthetic phenols have been designed as alternatives to BHT and BHA antioxidants. Influence of various substituents at the ortho, meta and para positions of the aromatic core of phenols on the bond dissociation enthalpy of the ArO–H bond was evaluated using a DFT method B3LYP/6-311++G(2d, 2p)//B3LYP/6-311G(d, p). This prediction highlighted the ortho -propenyl group as the best substituent to decrease the bond dissociation enthalpy (BDE) value. The rate constants of hydrogen transfer from these phenols to DPPH radical in a non-polar and non-protic solvent have been measured and were found to be in agreement with the BDE calculations. For o -propenyl derivatives from 2- tert -butyl-4-methylphenol, BHA, creosol, isoeugenol and di- o -propenyl p -cresol, fewer radicals were trapped by a single phenol molecule, i.e. a lower stoichiometric number. Reaction mechanisms involving the evolution of the primary phenoxyl radical ArO are proposed to rationalise these effects.